The Effect of Residential Proximity to the Beach and Industrial Area on the Incidence of Hypertension in Kendal District - Ayuningrum, Nyovita; Romadhon, Yusuf Alam (Journal La Medihealtico, 2024)
The hospital is one of the institutions engaged in health services. The Hypertension is when the results of systolic blood pressure (SBP) measurements are ≥140 mmHg and/or diastolic blood pressure (DBP) are ≥90 mmHg. According to the World Health Organization, hypertension in 2015 was around 1.13 billion and is estimated to be 1.5 billion in 2025. The prevalence in Indonesia in 2023 was around 30.8% and in Kendal it continues to increase every year. People living in coastal areas have risk factors for hypertension such as salt consumption, consumption of foods high in sodium (shrimp, dried fish and salted fish), and lack of physical activity. Various types of air pollutants such as particulate matter (PM) are widely recorded as being associated with cardiovascular disease, especially in industrial areas and big cities. Objective: This study is to analyze the effect of proximity to the beach and industrial areas on the incidence of hypertension in Kendal Regency. Method: This study uses observational analytics with a cross-sectional research design. The sampling technique used is purposive sampling. Univariate and bivariate analysis using the Chi-Square test. Results: Significant results were obtained based on the Chi-Square test on the effect of residence in coastal areas and industrial areas on the occurrence of hypertension with a p-value of 0.000 ( p-value <0.05). Conclusion: This study shows the effect of proximity to the beach and industrial areas on the incidence of hypertension in Kendal Regency.